Fashion, Design and Entertainment Law in Uganda - Lubogo, Isaac Christopher (Jescho Publishing House, 2022)
Fashion is literally defined to mean a popular or the latest style of clothing, hair, decoration or behaviour. Fashion law can be defined as an amalgamation of various kinds of laws, viz, contract law, employment law, consumer protection law, but most importantly intellectual property law, which can be regarded as the major tenet of fashion law. It also includes related areas such as textile production, modelling, media and the cosmetics and perfume industries. It is a specific field of law that deals with legal issues that impact the fashion industry. Fashion is a popular aesthetic expression in a certain time and context, especially in clothing, footwear, life style, accessories, make up, hairstyle and body proportions. A trend often connotes a specific aesthetic expression and often lasting shorter than a season. Style is an expression that lasts over many seasons and is often connected to cultural movements and social makers, symbols, class and culture. Fashion is generally transient of short lasting in nature and involves continuous change.
Keywords: Fashion law - Uganda; Entertainment law